Toxicity and waste management using bioremediation - Rathoure, Ashok K. 1983-; Dhatwalia, Vinod K. 1983- (Advances in environmental engineering and green technologies (AEEGT) book series, 2016)
This book provides relevant theoretical and practical frameworks and the latest empirical research findings on the remediation of contaminated soil and groundwater using bioorganisms.